Assessing the health state of arboreal vegetation in urban, rural, and natural ecosystems, using non–destructive phenotypic techniques: implications for conservation and management - Ζευγώλης, Ιωάννης (2024)
Conservation of urban, rural, and natural ecosystems, through effective monitoring of their health state, is crucial both at a tree and at a population level. In this thesis, a comprehensive methodological framework for estimating the health state of arboreal vegetation was established, by considering the trees’ fundamental phenotypic, spectral, spatial, thermal, and humidity traits. A set of 910 trees from nine different species was evaluated, by obtaining phenotypic information from (a) 334 urban trees (Robinia pseudoacacia, Morus alba, Melia azedarach), 80 olive trees (Olea europaea), and 496 pine trees (Pinus brutia). The effect of different disturbances such as structural defects and fungal presence, which can compromise the trees’ mechanical integrity, health, and productivity, was detected, quantified, and mapped, with the use of non–destructive phenotypic techniques. Results showed that combining the trees’ phenotypic traits and indices, can sufficiently (a) estimate decay severity, (b) classify hazardous trees, (c) identify fungal presence, and (e) predict the trees’ growth rate and productivity. All of these can contribute to tree health assessment, by offering significant information in monitoring urban, rural, and natural ecosystems’ dynamics.